Antimicrobial Efficacy of Fluoride Varnish with Quercetin against Candida albicans and Enterococcus faecalis: An In Vitro Study - Natarajan, Bhuvaneswari; Jeevanandan, Ganesh; Maganur, Prabhadevi C.; Assiry, Ali Ahmed; Syed, Ather Ahmed; Madkhali, Alfaroog; Manqari, Asim Ibrahim H.; Vishwanathaiah, Satish (European Journal of General Dentistry, 2025)
Objective Fluoride varnish is a preventive management of dental caries. Matrix metalloproteinases (MMPs) play a major role in the degradation of the extracellular matrix in the process of dental caries progression. Quercetin, a natural flavonoid, has a literature background with marked MMP inhibitor activity. Till date, there is no fluoride varnish that has both remineralizing effect and prevention of the dentin matrix breakdown at the same time. Therefore, a novel fluoride varnish containing tricalcium phosphate, quercetin, and sodium fluoride is formulated to have a greater remineralizing action while also preventing the deterioration of the dentinal matrix. So, this study aimed to evaluate the antimicrobial efficacy of the novel fluoride varnish with quercetin against Enterococcus faecalis and Candida albicans.Materials and Methods The novel fluoride varnish with quercetin was prepared and tested for potential applications. The antimicrobial activity of the prepared fluoride varnish with quercetin at different concentrations (25, 50, and 100 μL) against oral pathogens (E. faecalis and C. albicans) was evaluated using the agar well diffusion method, protein leakage assay, cytoplasmic leakage assay, and time kill curve assay.Results The novel fluoride varnish with quercetin showed significant inhibition zone against C. albicans and E. faecalis in the agar diffusion method. The protein leakage and cytoplasmic leakage assays showed dose-dependent relationships with increased antimicrobial action at higher concentrations of fluoride varnish with quercetin (p < 0.05).Conclusion The novel fluoride varnish with quercetin has better antimicrobial efficacy than the commercial fluoride varnish.
Keywords: quercetin; fluoride varnish; varnish; MMP inhibitor